Prosedur Penagihan Pajak Berdasarkan Surat Teguran dan Surat Paksa di Kantor Pelayanan Pajak Pratama Singaraja - Gusti Ayu Putu Putrika Yanti; Lucy Sri Musmini (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
The purpose of this study was to find out how the procedures for issuing tegutan and forced letters are at the Singaraja Pratama Tax Office. This research is a qualitative descriptive study. The data used are primary and secondary data obtained from interviews with the bailiff and related parties with the billing section. The method used in this research is documentation, interviews and literature study. The data analysis technique is a descriptive technique. The results of this study indicate that the issuance of warning letters and forced letters at KPP Pratama Singaraja uses the Standard Operating Procedure (SOP) that has been set by the Directorate General of Taxes as a reference for the implementation of warning letters and forced letters as tax collection actions. In its implementation, KPP Pratama Singaraja has carried out the SOP properly and is also in accordance with the Law of the Republic of Indonesia No.19 of 2000 concerning Tax Collection by Forced Letters. However, in the case of submitting warning letters and forced letters to the bailiff, they often encounter obstacles, including taxpayers who do not carry out taxes and the address of the taxpayer is not valid.